A Molecular Copper Catalyst for Electrochemical Water Reduction with a Large Hydrogen‐Generation Rate Constant in Aqueous Solution1. Issue 50 (14th October 2014) - Zhang, Peili; Wang, Mei; Yang, Yong; Yao, Tianyi; Sun, Licheng
Abstract The copper complex [(bztpen)Cu](BF4)2 (bztpen=N‐benzyl‐N, N′, N′‐tris(pyridin‐2‐ylmethyl)ethylenediamine) displays high catalytic activity for electrochemical proton reduction in acidic aqueous solutions, with a calculated hydrogen‐generation rate constant (kobs) of over 10000 s−1. A turnover frequency (TOF) of 7000 h−1 cm−2 and a Faradaic efficiency of 96 % were obtained from a controlled potential electrolysis (CPE) experiment with [(bztpen)Cu]2+ in pH 2.5 buffer solution at −0.90 V versus the standard hydrogen electrode (SHE) over two hours using a glassy carbon electrode. A mechanism involving two proton‐coupled reduction steps was proposed for the dihydrogen generation reaction catalyzed by [(bztpen)Cu]2+.